Exploring differences in electromyography and ground reaction forces between front and back squats before and after a fatiguing protocol - Rattley, K.; Bampouras, T. M.; Gaffney, C. J. (ISBS Proceedings Archive (Michigan), 2022)
Limited research has been conducted to explore differences in biomechanical and physiological demands of the front and back squat, especially in response to fatigue where technique may be altered. This study investigated differences in electromyography and ground reaction forces during a 3-repetition maximum back and front squat before and after a fatiguing protocol in 30 males. Mean and peak activation of the semitendinosus was greater in the back squat than the front squat (p < 0.05). There were no differences in quadricep activation between back and front squats. There were no differences in electromyography as a result of fatigue, however, force production decreased for back squats following fatigue (p < 0.01). This research disputed the notion that front squats have a greater quadricep focus, however lends support to the hypothesis that quadricep activation equal to the back squat can be achieved with lighter absolute load in a front squat. The finding of lower ground reaction forces for the back squat following the fatiguing protocol in addition to no differences in electromyography between front and back squats indicates greater effects of the fatiguing protocol on back squat performance.